2013
DOI: 10.1080/10705422.2013.842196
|View full text |Cite
|
Sign up to set email alerts
|

Using Photovoice to Empower Youth and Adults to Prevent Crime

Abstract: Photovoice empowers residents to use photographs to identify neighborhood concerns. Although Photovoice has been used to facilitate dialogue and action among residents to address a variety of issues, including neighborhood crime, it has not been used as part of an intervention to promote collective efficacy. This project integrated Photovoice into a crime-prevention program the goal of which was to facilitate collective efficacy, which. in turn, has been associated with lower levels of neighborhood crime and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…For example, C. C. Wang's (1999) study showed how photovoice can be used as an intervention strategy to empower women to improve their health in rural China. Ohmer and Owens (2013) illustrated how photovoice can be integrated into a crime prevention program to enhance the collective efficacy of community residents in crime prevention. Similarly, Suffla et al (2012) demonstrated how photovoice can empower young people to get involved in their community to enhance community safety.…”
Section: Introductionmentioning
confidence: 99%
“…For example, C. C. Wang's (1999) study showed how photovoice can be used as an intervention strategy to empower women to improve their health in rural China. Ohmer and Owens (2013) illustrated how photovoice can be integrated into a crime prevention program to enhance the collective efficacy of community residents in crime prevention. Similarly, Suffla et al (2012) demonstrated how photovoice can empower young people to get involved in their community to enhance community safety.…”
Section: Introductionmentioning
confidence: 99%
“…Photographs chosen by the research participant are utilized as the main prompts in open-ended interviewing (Crane, 2012). The researcher is not present during the photography, and thus the balance of power in this research phase shifts more toward the research participant (see also Ohmer & Owens, 2013), in this case a child or young person. Photo-narrative informants can be seen more as "active" than passive research participants (Kaplan, 2008).…”
Section: Photographing As a Participative Methodsmentioning
confidence: 99%
“…The photovoice process also relies on established partnerships with key community stakeholders, encourages the equitable inclusion of partners in the research process, and generally culminates in a community forum through which participants can articulate their perspectives to stakeholders and community members. This well‐established and broadly implemented methodology aligned with CBPR has previously been used to facilitate community work to identify priorities and advocacy efforts to address violence as broadly defined (Chonody, Ferman, Amitrani‐Welsh, & Martin, ; Hergenrather, Rhodes, Cowan, Bardhoshi, & Pula, ; Ohmer & Owens, ; Rhodes, Hergenrather, Wilkin, & Jolly, ; Strack, Magill, & McDonagh, ).…”
Section: The Projectmentioning
confidence: 99%
“…This well-established and broadly implemented methodology aligned with CBPR has previously been used to facilitate community work to identify priorities and advocacy efforts to address violence as broadly defined (Chonody, Ferman, Amitrani-Welsh, & Martin, 2013;Hergenrather, Rhodes, Cowan, Bardhoshi, & Pula, 2009;Ohmer & Owens, 2013;Rhodes, Hergenrather, Wilkin, & Jolly, 2008;Strack, Magill, & McDonagh, 2004).…”
Section: Photovoice and Adolescent Narrativesmentioning
confidence: 99%